(untitled) (Texas Journal of Multidisciplinary Studies, 2023)
The aim of present study is to evaluate the optimum mechanical and biological properties of Steel-based PLD (pulsed laser deposition) using Fuzzy AHP-TOPSIS- based Taguchi Approach. In order to evaluate the optimal option according to L8 Taguchi orthogonal array, the simplicity and high flexibility of PLD made it to be considered as one of the most popular mechanisms for coating. On the contrary with other deposition methods, the PLD deposition system can be settled without a complex instrumentation system, fabrication and other system required for deposition the PLD parameters were designed by considering three levels of process parameters (No. of pulse, voltage and distance between target and substrate) to evaluate the optimum characteristics of carbon steel in terms of mechanical properties and biological properties (microhardness and antibacterial tests).Titanium dioxide (TiO2) in nanostructured form was used widely in various applications, in this work the samples were coated with titanium oxide TiO2 in the form of powder. Finally, the Taguchi technique is useful and good for carefully planning tests and the fuzzy AHP-TOPSIS results manifested that the optimum results are voltage (900 V), No. of Pulse (900) and distance (5 cm), as well as the target parameters are microhardness (545.4 HV) and excellent biological results